A human rights-consistent approach to multidimensional welfare measurement applied to sub-Saharan Africa - Arndt, Channing; Mahrt, Kristi; Hussain, M. Azhar; Tarp, Finn (United Nations University, 2017)
The rights-based approach to development targets progress towards the realization of 30 articles set forth in the Universal Declaration of Human Rights. Progress is frequently measured using the multidimensional poverty index. While elegant and useful, the multidimensional poverty index is in reality inconsistent with the Universal Declaration of Human Rights principles of indivisibility, inalienability, and equality. We show that a first-order dominance methodology maintains consistency with basic principles, discuss the properties of the multidimensional poverty index and first-order dominance, and apply the measures to 26 African countries. We conclude that the multidimensional poverty index and first-order dominance are useful complements that should be employed in tandem.